Age Modulates the Effects of Mental Fatigue on Typewriting - de Jong, Marlon; Jolij, Jacob; Pimenta, André; Lorist, Monicque M. (Frontiers in Psychology, 2018)
In the present study, we examined whether age influences the effects of mental fatigue on task performance, and if we could validate the use of measures based on typing behaviour as an index of the effects of mental fatigue on different aspects of cognition. Young (N=24, 18-30y) and middle-aged (N=24, 50-67y) participants performed a typewriting task and a mouse targeting task for 120 minutes. At the beginning and at the end of the experiment the level of subjective fatigue was assessed. During task performance measures based on typing behaviour and EEG were recorded. Results showed that subjective fatigue increased over the experiment in both the young and the middle-aged group. Typing speed decreased with time-on-task in both age groups, reflected in larger general interkey intervals and in an increase in typing time. In addition, typing accuracy decreased with time-on-task in the young group, however, not in the middle-aged group, reflected by an increase in typing errors. Moreover, the young group used the backspace key more often with time-on-task due to delayed error-correction, reflected in larger backspace sequences, resulting in larger interkey intervals and increased typing time. This effect was absent in the middle-aged group. In the young group, the P3 brain potential amplitude decreased over the experiment, which was related to an increase in typing time, longer general interkey intervals, and an increase in typing errors, suggesting that decreased task engagement was related to less efficient typewriting, at least in the young group. These results indicate that measures based on typing behaviour could give information about the process of mental fatigue, and in addition suggest that age influences the effect of mental fatigue on typewriting. More specifically, younger adults more often adopt a strategy that emphasize speed, while middle-aged adults act more error-aversive than younger adults.